Temporal variability in the abundance of the bay anchovy Anchoa mitchilli (Valenciennes, 1848) eggs and spawning biomass in Pueblo Viejo Lagoon, Veracruz, Mexico - Sánchez-Ramírez, Marina; Ocaá-Luna, Alberto (HIDROBIOLÓGICA, 2017)
The spawning of Anchoa mitchilli is analyzed and its adult biomass is estimated in Pueblo Viejo Lagoon, Veracruz, Mexico. Samples were collected at 19 stations in October and December of 1992, in March, April, June and August of 1993, using a zooplankton net with a 505 µm mesh size and a 50 cm mouth to which a flowmeter was fixed. The spawning of A. mitchilli was analyzed with respect to the abundance of eggs in the lagoon (number of eggs/m3), and the adult biomass was calculated through the annual production of eggs. A total of 51,348 eggs was obtained of which 50,205 (97.7%) corresponded to A. mitchilli. This is a species that spawns inside the lagoon throughout the year, except during the rains (July-October), with a peak (96.8%) in March-April in temperatures of 19-20ºC and salinities of 14-21 psu. Temperature (15-32ºC) was observed to be one of the main factprs that determine the spawning period, whereas salinity inhibits spawning below 10 psu. A. mitchilli biomass in Pueblo Viejo Lagoon was 793 metric tons and 5.7 g/m3. A latitudinal gradient from north to south is evident for the biomass of this species, and this is determined by an increase inthe diversity towards the tropical regions and the resulting decrease in the biomass of the species, down to the southern limit of its distribution in the Peninsula of Yucatan, Mexico.